In vitro and in silico investigation of caprylic acid effect on multi drug resistant (MDR) Klebsiella pneumoniae biofilm. Issue 2 (22nd January 2020) - Gupta, Abhishek; Cheepurupalli, Lalitha; Vigneswaran, S.; Singh Rathore, Sudarshan; Suma Mohan, S.; Ramakrishnan, Jayapradha
Abstract: Communicated by Ramaswamy H. Sarma